Role of STN1 and DNA polymerase α in telomere stability and genome-wide replication in Arabidopsis - Derboven, Elisa; Ekker, Heinz; Kusenda, Branislav; Bulankova, Petra; Riha, Karel (PLoS genetics, 2014)
The CST (Cdc13/CTC1-STN1-TEN1) complex was proposed to have evolved kingdom specific roles in telomere capping and replication. To shed light on its evolutionary conserved function, we examined the effect of STN1 dysfunction on telomere structure in plants. STN1 inactivation in Arabidopsis leads to a progressive loss of telomeric DNA and the onset of telomeric defects depends on the initial telomere size. While EXO1 aggravates defects associated with STN1 dysfunction, it does not contribute to the formation of long G-overhangs. Instead, these G-overhangs arise, at least partially, from telomerase-mediated telomere extension indicating a deficiency in C-strand fill-in synthesis. Analysis of hypomorphic DNA polymerase α mutants revealed that the impaired function of a general replication factor mimics the telomeric defects associated with CST dysfunction. Furthermore, we show that STN1-deficiency hinders re-replication of heterochromatic regions to a similar extent as polymerase α mutations. This comparative analysis of stn1 and pol α mutants suggests that STN1 plays a genome-wide role in DNA replication and that chromosome-end deprotection in stn1 mutants may represent a manifestation of aberrant replication through telomeres.
Keywords: Genome, Plant; Heterochromatin; DNA Replication; replikace DNA; DNA Polymerase I; genom rostlinný; chromozomální proteiny, nehistonové; mutace; Arabidopsis Proteins; heterochromatin; exodeoxyribonukleasy; Cell Cycle Proteins; proteiny huseníčku; Exodeoxyribonucleases; proteiny buněčného cyklu; Mutation; DNA-polymerasa I; telomerasa; Chromosomal Proteins, Non-Histone; Telomerase; Telomere; telomery; Arabidopsis